The fuzzy logic applied to the formation of effective clusters: the case of mezcal companies of Michoacan - Godínez Reyes, Norma Laura; Alfaro García, Víctor G.; Gómez Monge, Rodrigo; Alfaro Calderón, Gerardo (2021)
The challenges faced by the companies in the face of globalization have resulted in greater intensity and diversity of competition, causing great uncertainty for companies and to a greater degree for Micro, Small and Medium business (MSMEs), including fruit and vegetable companies where the mezcal industry is located. In the present work, the theory of affinities proposed by Kaufmann and Gil-Aluja is applied in order to identify subgroups of mezcal companies in the state of Michoacán according to their affinity, allowing them to form clusters in order to create synergies and thus create or enhance their competitive advantages.